Peran Modal Sosial Pada Kelompok Tani Tamporok Di Desa Klabat Kecamatan Dimembe Kabupaten Minahasa Utara - Togelang, Wehelmina; Tambas, Jane Sulinda; Timban, Jean Fanny Juanita (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
TThis study aims to understand and describe the role of social capital in farmer groups in Klabat Village, Dimembe District, North Minahasa Regency. The research was conducted from April to June 2024. Data was collected through questionnaires, interviews, and documentation. Primary data was collected directly by the researcher through interviews and questionnaires completed by respondents, while secondary data was obtained from other parties related to the research and sourced from the village office. The research method used was descriptive analysis. The results showed that the role of social capital in the Tamporok farmer group, specifically in the variables of trust, social networks, and social norms, was categorized as very significant.